Peer review in an Era of Evaluation Understanding the Practice of Gatekeeping in Academia - Forsberg, Eva; Geschwind, Lars; Levander, Sara; Wermke, Wieland (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access volume explores peer review in the scientific community and academia. While peer review is as old as modern science itself, recent changes in the evaluation culture of higher education systems have increased the use of peer review, and its purposes, forms and functions have become more diversified. This book put together a comprehensive set of conceptual and empirical contributions on various peer review practices with relevance for the scientific community and higher education institutions worldwide. Consisting of three parts, the editors and contributors examine the history, problems and developments of peer review, as well as the specificities of various peer review practices. In doing so, this book gives an overview on and examine peer review , and asks how it can move forward. Eva Forsberg is Professor of Education at Uppsala University, Sweden. Her research focuses education governance and evaluation, academicwork and the interface between educational policy, practice and research. Lars Geschwind is Professor in Engineering Education Policy and Management at KTH Royal Institute of Technology, Sweden. His main research interests are higher education policy, institutional governance, academic leadership and academic work. Sara Levander is Senior Lecturer and Researcher in Education at Uppsala University, Sweden. Her research interests are higher education, academic work and faculty evaluation in academic recruitment and promotion. Wieland Wermke is Associate Professor in Special Education at Stockholm University, Sweden. His research interest focuses on comparative education methodology, and teacher practice at different levels of education.